Building a Worm Wheel Model by Simulation of Gear Cutting Process - Urinov Nasillo Fayzilloevich; Dubrovets Lyudmila Vladimirovna; Ergashov Zaxriddin Mustakimovich (Genius Journals, 2022)
The article presents one of the ways to build a model of a worm wheel in solidworks by simulating the process of gear cutting using the rolling method.
Keywords: Worm; workpiece; modeling; tooth profile